Unique Common Fixed Points for Two Weakly $C^*$-Contractive Mappings on Partially Ordered 2-Metric Spaces (Communications in Mathematical Research, 2020)
In this paper, we give existence theorems of common fixed points fortwo mappings with a weakly $C^*$-contractive condition on partially ordered 2-metricspaces and give a sufficient condition under which there exists a unique common fixedpoint.
Keywords: 2-metric space; weak $C^*$-contraction; common fixed point